Why do referees end their careers and which factors determine the duration of a referee`s career? - Rullang, C.; Emrich, E.; Pierdzioch, C. (Current Issues in Sport Science, 2017)
Against the background that the number of referees has been falling in recent years, the German Football Association (DFB) needs to answer two key questions: (i) Why do referees end their careers, and, (ii) which factors determine the duration of referee careers? We studied these questions using data from a questionnaire study of former referees. Results of estimating linear regression models and a Cox model show that the duration of a typical referee career depends, among other factors, on how a referee thinks that the career developing according to his or her plan, and on whether the referee is successful in coping with insults, threats, and violence. The "survival rate" of a referee increases in the subjective evaluation of the importance of football-specific know-how. Approximately 39 % of the former referees stated that the end of their referee career could have been prevented.